Challenging Case of Ectopic ACTH Secretion from Prostate Adenocarcinoma - Wanling Zeng; Joan Khoo (Case Reports in Endocrinology)
Cushing’s syndrome (CS) secondary to ectopic adrenocorticotrophic hormone (ACTH)-producing prostate cancer is rare with less than 50 cases reported. The diagnosis can be challenging due to atypical and variable clinical presentations of this uncommon source of ectopic ACTH secretion. We report a case of Cushing’s syndrome secondary to prostate adenocarcinoma who presented with symptoms of severe hypercortisolism with recurrent hypokalaemia, limb oedema, limb weakness, and sepsis. He presented with severe hypokalaemia and metabolic alkalosis (potassium 2.5 mmol/L and bicarbonate 36 mmol/L), with elevated 8 am cortisol 1229 nmol/L. ACTH-dependent Cushing’s syndrome was diagnosed with inappropriately normal ACTH 57.4 ng/L, significantly elevated 24-hour urine free cortisol and unsuppressed cortisol after 1 mg low-dose, 2-day low-dose, and 8 mg high-dose dexamethasone suppression tests. 68Ga-DOTANOC PET/CT showed an increase in DOTANOC avidity in the prostate gland, and his prostate biopsy specimen was stained positive for ACTH and markers for neuroendocrine differentiation. He was started on ketoconazole, which was switched to IV octreotide in view of liver dysfunction from hepatic metastases. He eventually succumbed to the disease after 3 months of his diagnosis. It is imperative to recognize prostate carcinoma as a source of ectopic ACTH secretion as it is associated with poor clinical outcomes, and the diagnosis can be missed due to atypical clinical presentations.